AlGaN/GaN high-electron-mobility transistor pH sensor with extended gate platform - Pyo, Ju Young; Jeon, Jin Hyeok; Koh, Yumin; Cho, Chu young; Park, Hyeong Ho; Park, Kyung Ho; Lee, Sang Woon; Cho, Won Ju (AIP Advances, 2018)
In this paper, we fabricated an AlGaN/GaN high electron mobility transistor (HEMT) pH sensor with an extended-gate (EG). As the carrier mobility of the transducer that is used as the biosensor is increased, the electrical signal conversion efficiency of the biomaterials is improved. Therefore, the HEMT is a more suitable transducer platform than the conventional silicon-based transistor. The fabricated AlGaN/GaN device showed an electron density of 9.0 × 1012 cm-2, and an electron mobility of 1,990 cm2/V-s. In order to reduce the gate leakage current, which is a drawback of conventional HEMT devices, we deposited a 3-nm thick Al2O3 layer as a top-gate oxide by the atomic layer deposition (ALD) method; the fabricated HEMT has a metal-insulator semiconductor (MIS) structure. In addition, we used the EG to implement the disposable biosensor. Although the EG (a sensing membrane) is contaminated and destroyed, the HEMT (a transducer) can be reused. We evaluated the pH sensing characteristics using a pH sensor, which was implemented by connecting the HEMT and EG. The EG HEMT pH sensor showed a sensitivity of 57.6 mV/pH, which is close to the Nernst limit (approximately 59 mV/pH), and a linearity of 98.93%. To verify the stability and reliability of the implemented EG HEMT pH sensor, we measured the real-time response. The EG HEMT pH sensor has an error of only 2.39% of the signal. Therefore, we expect that the EG-based AlGaN/GaN HEMT pH sensor will be a suitable next-generation biosensor platform for a high electrical signal change efficiency of biomaterials, disposable, and point-of-care systems.
Keywords: AlGaN/GaN high electron mobility transistors; Bio-sensor platforms; Disposable biosensor; Gate-leakage current; Metal insulator semiconductor structures; Point-of-care systems; Silicon-based transistors; Stability and reliabilities